Robust classification of dental tissues using LIBS data based on data reconstruction and distance prior strategy - Shuting Lin; Xingwei Yi; Lei Yan; Shanshan Liang; Fusong Yuan (Analytica Chimica Acta, 2026)

Assessing roof retrofit cooling potential under synergistic climate–urbanization impacts in Wuhan: An integrated WRF-based framework using PLUS-predicted LCZs - Xilin Zhou; Shuangjiang Peng; Zhengyuan Xu; Shuting Yan (Sustainable Cities and Society, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

pH/temperature dual-responsive antifungal delivery system based on polydopamine-modified montmorillonite for sustained essential oil release - Guixiang Teng; Hongyu Wang; Shuting Zhang; Mengyuan Yu; Yanzan Meng; Meng Zhao; Yan Yang; Peng Pu; Chun Zhang (Applied Clay Science, 2026)

A Trajectory–Activity Vitality Framework for Neighborhood Open Spaces: Linking Spatial Attributes and Microclimate with Pedestrian Movement and Activity Patterns - Chuancheng LI; Zhiling ZHU; Shuting Yan; Xilin ZHOU (Building and Environment, 2026)

Targeting IL-33 in Precision Neuroimmunology: Cellular Mechanisms and Therapeutic Strategies for CNS Disorders - Lili Li; Shuting Wang; Lian Duan; Luyu Zhang; Hongmu Yan; Yue Zhu; Luyang Tao; Yuan Gao (Journal of Neuroimmune Pharmacology, 2026)

Study on the Effects and Mechanisms of Resveratrol in Improving Cognitive Impairment in Aβ1−42-Induced Alzheimer’s Disease Model Mice - Chu Zhang; Yunhan Ma; Zhidan Shi; Xinqi He; Jiayi Hu; Shuting Chen; Hao Wu; Meng Tian; Chuang Yan; Mengtao Xing; Ling He (Journal of Neuroimmune Pharmacology, 2026)

Dynamics of kinetic energy in rill headcut erosion and sediment yield characteristics within granitic red soil regions - Shuyu Luo; Jianyu Wang; Zhe Lin; Jiangxing Wei; Wencong Liang; Hongyu Liu; Fang Wang; Guiwan Yan; Shuting Liu; Xiaoqian Duan; Yusong Deng (CATENA, 2026)

Mixed exposure to brominated flame retardants adversely affects vaccine-induced antibody titers: Risk prioritization and benchmark dose modeling - Zihui Zhao; Chi Zhang; Xueyu Chen; Yongheng Yan; He Jiao; Xianhao Wang; Ruxu Yan; Yiqian Wang; Meng Liu; Xianfeng Yue; Yuqian Sui; Xia Li; et al. (Toxicology Letters, 2026)

A machine learning-based model for soil iron oxides estimation using fused hyperspectral and multispectral data - Yongshi Tan; Zhenxi Wei; Yan Xiao; Yulin Huang; Zongxin Li; Shuting Yang; Lin Zou; Lanhui Yang; Yusong Deng (Journal of Soils and Sediments, 2026)

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

Leveraging soil quality assessment for Cd-contaminated farmland through a diagnostic quantitative analysis of multi-dimensional indicators - Yu Gao; Shuting Xiang; Xiulan Yan; Rugang Wang; Xiao Yang (Journal of Hazardous Materials, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Integrative engineering of biomass-derived CQDs for enhancing photosynthesis of microalgae coupled with bioethanol production - Xiaofeng Liu; Youlian Xu; Yuantao Shen; Jingwen Zhang; Weiyan Zhang; Shuting Ke; Yadong Zhao; Boyang He; Meihua Fan; Zengliang Miao; Xiaolin Zhang; Zhi Liao; et al. (Bioresource Technology, 2026)

Stability and Transport of Ferrihydrite Nanoparticles in Alkaline Soils - Yan Gong; Meiling Wang; Shuting Tian; Qingwei Ding; Xia Li; Gaiqiang Yang; Qi Liu; Juanfang Yang; Lijuan Huo (Water, Air, & Soil Pollution, 2026)

Essential oil-loaded amine-modified HNTs composites for sustained release and enhanced antibacterial performance in root rot control - Guixiang Teng; Hui Yao; Hongyu Wang; Shuting Zhang; Yanzan Meng; Meng Zhao; Yan Yang; Chun Zhang (Applied Clay Science, 2026)

Characteristics and controlling factors of soil micro-climate in a subtropical re-vegetation catchment: Insights from continuous moisture and temperature observations - Jiapan Xu; Muxing Liu; Siqi Mei; Qian Yang; Jun Zhang; Jun Yi; Shuting Ding; Yan Tan (Plant and Soil, 2026)

Sprint interval training for cardiovascular prevention: a time-efficient alternative or an overstated promise? An umbrella review - Weibao Liang; Chuannan Liu; Shuting Xu; Shuhui Ma; Yue Zong; Xujie Yan (European Journal of Applied Physiology, 2026)

The potential of AI global weather models for reference evapotranspiration forecasting: a comparison with numerical weather prediction models - Shuting Zhao; Yuan Qiu; Zihuang Yan; Lifeng Wu; Rangjian Qiu; Yufeng Luo (Journal of Hydrology, 2026)

Ultra-stable crease-structured paper pressure sensor with ultra-low detection limit for wind sensing and real-time texture recognition - Yugang Chen; Shasha Wang; Yan Li; Mengyu Cao; Xun Fu; Shuting Xie; Jiangtian Tan; Huan Gao; Linghai Xie (Chemical Engineering Journal, 2025)

Influence of initial headcut height on rill headcut erosion mechanisms via runoff hydrodynamics modulation in granite residual soil - Jianyu Wang; Zhe Lin; Jiangxing Wei; Wencong Liang; Hongyu Liu; Fang Wang; Guiwan Yan; Shuting Liu; Xiaoqian Duan; Yusong Deng (Journal of Hydrology, 2025)

An antifouling electrochemiluminescence sensor based on Mn-NiFe-MOF/NFF self-supporting electrode with oxygen evolution reaction enhanced luminol-H2O system for sensitive detection of neomycin in water samples - Jia Wang; Shuting Lv; Yuran Zhao; Yan Ding; Qiongwei Wu; Wenxin Qu; Xianzhen Song; Lu Zhao; Caifeng Ding (Chemical Engineering Journal, 2025)

Cognitive experiments on labelling uncertainty for LCZ mapping across heterogeneous megacities in China: Introducing multi-source geospatial data and LCZ subclasses - Xilin Zhou; Jinyang Hu; Shuting Yan; Chuancheng Li (Urban Climate, 2025)

Characteristics, sources and risk assessment of volatile organic compounds in a subway environment - A case study in Xi’an, China - Meng Xiu; Yan Cheng; Shuting Liu; Yu Huang; Yonggang Xue; Yan Li; Yanan Meng; Rohan Jayaratne; Xianyu Wang; Phong K. Thai; Alma Lorelei de Jesus; Lidia Morawska (Building and Environment, 2025)

Validity of Smartwatches for Estimating Energy Expenditure During Aerobic Dance - Xueyuan Zhao; Xingyi Ding; Junchao Yang; Shuting Yan; Hong Wang; Kuan Tao; Junqiang Qiu (Journal of Science in Sport and Exercise, 2025)

Konjac glucomannan/xanthan gum hydrogels loaded with metal-phenolic networks encapsulated probiotic to promote infected wound healing - Qingxin Wu; Zhengfeng Lu; Lantao Wang; Shuting Peng; Zhengxiao Wang; Yan Qiu; Zhengping Liao; Yarong Wang; Xiaofei Qin (Carbohydrate Polymers, 2025)

Knockdown of the Clock gene in the liver aggravates MASLD in mice via inhibiting lipophagy - Shuhong Yang; Xinxin Ren; Jia Liu; Yan Lei; Minqian Li; Fang Wang; Shuting Cheng; Junjie Ying; Jie Ding; Xiaohui Chen (Molecular and Cellular Biochemistry, 2025)

A novel directed enzymolysis strategy for the preparation of umami peptides in Stropharia rugosoannulata and its mechanism of taste perception - Daoyou Chen; Mingli Rong; Shuting Tang; Chuanxi Zhang; Hao Wei; Zhaoting Yuan; Tingwei Miao; Hucheng Song; Haiming Jiang; Yan Yang; Lujia Zhang (Food Chemistry, 2025)

Transition metal doping of topological insulator Bi2Te2Se for application in zinc-ion batteries - Binbin Liu; Shuting Wang; Kemeng Yan; Yangyang Chen; Yuhui Ren; Haohui Xia; Ruiyong Chen; Junfeng Yan; Gang Wang (Chemical Engineering Journal, 2025)

Base-driven dehydrohalogenation coupled with catalytic hydrodehalogenation as a novel strategy for rapid dehalogenation of halogenated organic compounds containing aliphatic C-X bonds - Shuting Qin; Chen Wu; Xuanxuan Ma; Sujing Liu; Ying Liu; Qing Li; Bingfei Yan; Chuanhai Xia (Journal of Environmental Chemical Engineering, 2024)

Soil application of graphitic carbon nitride nanosheets alleviate cadmium toxicity by altering subcellular distribution, chemical forms of cadmium and improving nitrogen availability in soybean (Glycine max L.) - Kai Xu; Lifan Zheng; Kaifei Chu; Chenghua Xing; Jiajing Shu; Keming Fang; Shuting Ma; Yong Fang; Jianfang Yan; Miaozhen Cai; Xi-Lin Wu (Journal of Environmental Management, 2024)

Assessment of the estimation methods of Tmrt in semi-outdoor spaces in humid sub-tropical climates: An empirical study in Wuhan, China - Chuancheng Li; Kui Xu; Shuting Yan; Qunfeng Ji; Dongfang Zhang; Xilin Zhou (Building and Environment, 2024)

Investigation on the thermodynamic performance and machinery mass in the N2O-based mixtures recompression Brayton cycle for a nuclear-powered spacecraft - Xinyu Miao; Haochun Zhang; Shuting Zhao; Cheng Zhang; Yan Xia (Annals of Nuclear Energy, 2024)

First Record of Partial Albinism in the Chinese Fanray, Platyrhina Sinensis (Elasmobranchii: Myliobatiformes: Platyrhinidae) - Yan Zhuang; Shuting Ke; Mingru Chen; Jiamei Xiao (Thalassas: An International Journal of Marine Sciences, 2024)
A female albino fanray specimen was collected by trawl from the southern Taiwan Strait on April 11, 2022. This unique individual was identified as the Chinese fanray, Platyrhina sinensis (Bloch & Schneider, 1801), based on morphological identification and DNA barcoding. It was classified as partial albinism (leucism) due to the absence of pigmentation in the skin and normal pigmentation in the irises. This specimen represents the first reported case of albinism within the family Platyrhinidae, providing valuable insights for physiological and ecological research on albino fish.

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Assessing the thermal risks for residents and visitors in traditional Street-facing Dwellings with Eaves Gallery during an extreme heatwave event - Shuting Yan; Jing He; Shuangjiang Peng; Zehua Fang; Xilin Zhou (Building and Environment, 2024)

Medium-chain triglyceride-stabilized docetaxel-loaded HSA nanoparticles effectively inhibited metastatic non-small cell lung cancer - Yunlong Cheng; Xiaoying Pang; Jing Wu; Lingling Zhou; Jinxu Cao; Liuchang Wang; Kang Qian; Peng Yang; Minjun Xu; Dongyu Sheng; Ran Meng; Pengzhen Wang; et al. (Drug Delivery and Translational Research, 2023)

Structure and anti-inflammatory activity of neo-clerodane diterpenoids from Scutellaria barbata - ShuTing Li; Dan Xu; Jing Jia; Wenbo Zou; JieYing Liu; Yao Wang; Kun Zhang; Xi Zheng; Yan-Yan Ma; Xuejian Zhang; Deng-Gao Zhao (Phytochemistry, 2023)

Graphitic carbon nitride alleviates cadmium toxicity to microbial communities in soybean rhizosphere - Jianfang Yan; Liping Wang; Chenghua Xing; Shuting Ma; Junzhe Xu; Beiyi Shou; Shasha Lan; Xilin Wu; Miaozhen Cai (Environmental Science and Pollution Research, 2023)

Blood-based biomarkers for Alzheimer’s disease: a multicenter-based cross-sectional and longitudinal study in China - Feng Gao; Linbin Dai; Qiong Wang; Chang Liu; Kexue Deng; Zhaozhao Cheng; Xinyi Lv; Yan Wu; Ziyi Zhang; Qingqing Tao; Jing Yuan; Shiping Li; et al. (Science Bulletin, 2023)

Removal of Zn2+ from glycolytic monomers of the polyethylene terephthalate based on electrodeposition - Wenxia Hou; Yi Li; Shuting Xu; Qian Wang; Kuntong Song; Junhong Liu; Nan Wang; Qing Zhou; Dongxia Yan; Xingmei Lu (Journal of Environmental Chemical Engineering, 2023)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Identification and characterization of a novel carboxylesterase EstQ7 from a soil metagenomic library - Zhenzhen Yan; Liping Ding; Dandan Zou; Luyao Wang; Yuzhi Tan; Shuting Guo; Yingchen Zhang; Zhihong Xin (Archives of Microbiology, 2021)

Molecular characterization of miRNA genes and their expression in Dimocarpus longan Lour - Yuling Lin; Yan Chen; Youjing Zeng; Shuting Zhang; Zihao Zhang; YuKun Chen; Jiawei Gong; Zhongxiong Lai (Planta, 2021)

Temporal characteristics detection and attribution analysis of hydrological time-series variation in the seagoing river of southern China under environmental change - Lihua Chen; Yan Wang; Billel Touati; Haopeng Guan; Gang Leng; Weifu Liu; Shuting Lv; Shuping Huang; Zihao Pan (Acta Geophysica, 2018)

Molecular characterization of heat–shock protein 90 gene and its expression in Gobiocypris rarus juveniles exposed to pentachlorophenol - Qiuping Liu; Shuting Huang; Chuan Deng; Li Xiong; Xiang Gao; Yun Chen; Chunqing Niu; Yan Liu (Fish Physiology and Biochemistry, 2015)